2012
DOI: 10.1159/000341154
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Asthma in Kuwait

Abstract: Objective: To evaluate the direct costs of treating asthma in Kuwait. Materials and Methods: Population figures were obtained from the 2005 census and projected to 2008. Treatment profiles were obtained from the Asthma Insights and Reality for the Gulf and Near East (AIRGNE) study. Asthma prevalence and unit cost estimates were based on results from a Delphi technique. These estimates were applied to the total Kuwaiti population aged 5 years and over to obtain the number of people diagnosed with asthma. The es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…The results of two studies about the prevalence of asthma in Jordan indicated its prevalence of 8.7–10% in 6–7 years, 4.1% in 6–12 years and 8.8–9.5% in 13–14 years childeren . The results of three studies showed moderate prevalence of asthma in Kuwaiti's children . The prevalence of asthma was 13.4–27.6% in 13–14 years and 18% in 5–16 years old children (Tables and , Figure ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The results of two studies about the prevalence of asthma in Jordan indicated its prevalence of 8.7–10% in 6–7 years, 4.1% in 6–12 years and 8.8–9.5% in 13–14 years childeren . The results of three studies showed moderate prevalence of asthma in Kuwaiti's children . The prevalence of asthma was 13.4–27.6% in 13–14 years and 18% in 5–16 years old children (Tables and , Figure ).…”
Section: Resultsmentioning
confidence: 95%
“…The prevalence of asthma was higher in females than males . The prevalence of asthma in adult population of Kuwait was also 15% . Asthma prevalence among Omani adults was associated with smoking and allergy…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, oral or intravenous treatment can increase the costs [16,17]. Treatment with a β 2 -agonist can reduce serum levels of Mg 2+ via urinary loss or intracellular shift [18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite remarkable advances in the understanding of asthma pathogenesis, diagnosis, and availability of medication [1], there is a group of asthmatic patients who are still poorly controlled despite receiving the maximal available treatment [1,2]. Previous studies reported that the disease pathogenesis of 50-80% of difficult-to-treat asthma patients involves an IgE-mediated mechanism that triggers allergic inflammation [3,4].…”
Section: Introductionmentioning
confidence: 99%